2022
DOI: 10.1101/2022.03.10.22272100
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Bebtelovimab, alone or together with bamlanivimab and etesevimab, as a broadly neutralizing monoclonal antibody treatment for mild to moderate, ambulatory COVID-19

Abstract: BACKGROUND: Bebtelovimab is a potent, fully human IgG1 monoclonal antibody (mAb) targeting the S-protein of SARS-CoV-2, with broad neutralizing activity to all currently known SARS-CoV-2 variants of concern, including omicron variant lineages. Specialized developmental approaches accelerated the initiation of a clinical trial designed to evaluate the efficacy and safety of bebtelovimab alone (BEB) or together with bamlanivimab (BAM) and etesevimab (ETE) delivered via slow intravenous push for the treatment of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
78
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(82 citation statements)
references
References 28 publications
2
78
0
2
Order By: Relevance
“…The RCTs differed in the percentage of participants with risk factors for progression to severe COVID-19. All RCTs except bebtelovimab 21 and CSSC-004 10 had more than 60% of participants at high-risk of COVID-19 progression, with the small chemical antiviral RCTs having nearly 100% high-risk participants. Diabetes mellitus was represented in 10 to 20% of most RCTs.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The RCTs differed in the percentage of participants with risk factors for progression to severe COVID-19. All RCTs except bebtelovimab 21 and CSSC-004 10 had more than 60% of participants at high-risk of COVID-19 progression, with the small chemical antiviral RCTs having nearly 100% high-risk participants. Diabetes mellitus was represented in 10 to 20% of most RCTs.…”
Section: Resultsmentioning
confidence: 99%
“…A fifth RCT was run in The Netherlands 16 , published as combined analysis with the Spanish RCT 16 . Five monoclonal antibody RCTs (bamlanivimab 2 , bamlanivimab/ etesevimab 17 , casirivimab/ imdevimab 18 , sotrovimab 19,20 , and bebtelovimab 21 ) led to initial FDA emergency use authorizations with regdanvimab 22 approved in Europe. Three outpatient RCTs of small chemical antivirals - oral molnupiravir 7 , oral nirmatrelvir/ritonavir 6 and intravenous remdesivir 23 led to emergency authorization.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In vitro studies showed that it retained the binding to S proteins with a broad range of virus variants. Clinical evaluation on the effect of Bebtelovimab alone or together with other monoclonal antibodies Bamlanivimab and Etesevimab is ongoing [ 92 , 93 ]. It has been recommended as an alternative option for managing COVID-19 only when the preferred small molecules Ritonavir-boosted nirmatrelvir and Remdesivir are not available.…”
Section: Antiviral Antibodiesmentioning
confidence: 99%